2015
DOI: 10.1186/s12870-015-0450-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolic and transcriptional analysis of a doubled diploid and its diploid citrus rootstock (C. junos cv. Ziyang xiangcheng) suggests its potential value for stress resistance improvement

Abstract: BackgroundPolyploidy has often been considered to confer plants a better adaptation to environmental stresses. Tetraploid citrus rootstocks are expected to have stronger stress tolerance than diploid. Plenty of doubled diploid citrus plants were exploited from diploid species for citrus rootstock improvement. However, limited metabolic and molecular information related to tetraploidization is currently available at a systemic biological level. This study aimed to evaluate the occurrence and extent of metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 83 publications
(96 reference statements)
5
60
0
2
Order By: Relevance
“…In the present study, all neopolyploid plants showed shorter plant height and less diameter of trunk than their parent diploid plants, probably due to the increase of ploidy level derived from somatically doubled by colchicines treatment, as previous reports that somatically doubled diploids exhibit slower growth rates, reduced vigor than their diploid counterparts in potato (Chen, 2010), tetraploid plants had smaller plant height than diploid plants of the same cultivar (Garbutt and Bazzaz, 1983;Jaskani et al, 2002;Tan et al, 2015). This revealed that polyploidization of plant is not always superiority, the negative side effects of polyploidization such as stunting and malformation also occurred (Eeckhaut et al, 2004).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the present study, all neopolyploid plants showed shorter plant height and less diameter of trunk than their parent diploid plants, probably due to the increase of ploidy level derived from somatically doubled by colchicines treatment, as previous reports that somatically doubled diploids exhibit slower growth rates, reduced vigor than their diploid counterparts in potato (Chen, 2010), tetraploid plants had smaller plant height than diploid plants of the same cultivar (Garbutt and Bazzaz, 1983;Jaskani et al, 2002;Tan et al, 2015). This revealed that polyploidization of plant is not always superiority, the negative side effects of polyploidization such as stunting and malformation also occurred (Eeckhaut et al, 2004).…”
Section: Discussionmentioning
confidence: 56%
“…Polyploids often show novel phenotypes that are not present in their diploid progenitors, or exceed the range of the contributing species (Levin, 1983;Ramsey and Schemske, 2002 ). Some of these traits, such as compact growth habit, increased drought resistance and stress resistance, apomixis (asexual seed production), pest resistance, flowering time, organ size and biomass, could allow polyploids to enter new niches or enhance their chances of being selected for use in agriculture (Comai 2005;Lu et al, 2006;Laere et al, 2011;Osborn et al, 2003;Pires et al, 2004;Ranney 2006;Ramsey and Schemske 2002;Tan et al, 2015;Viehmannova et al, 2012). The tetraploid fruit plants are shorter than diploid and are usually used as dwarf rootstocks (Webster, 1996) or breeding parents in triploid breeding programs (Jaskani and Khan, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…It has been previously suggested that tetraploids frequently occur in apomictic genotypes of citrus and related genera (Aleza et al ., ; Tan et al ., ). This implies that tetraploids can be identified in natural seedlings derived from apomictic plants.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, seedlings derived from the naturally derived embryo can be used to identify potential polyploids. As a matter of fact, tetraploids of citrus and trifoliate orange have been successfully obtained using this method (Aleza et al ., ; Tan et al ., ). Our results confirmed that this is an efficient approach for exploring tetraploids.…”
Section: Discussionmentioning
confidence: 97%
“…Through gene-dosage and epigenetic effects, together with nuclear enlargement, polyploidy causes genetic changes that result in pronounced phenotypic alterations (Comai 2005;Sun et al 2009;Van Laere et al 2011;Allario et al 2013;Hao et al 2013). Morphological effects commonly associated with polyploidy are bigger flowers, an altered leaf length-to-width ratio and changes in size and density of stomata (Sun et al 2009;Van Laere et al 2011;Trojak-Goluch, Skomra 2013;Tan et al 2015). Other frequently occurring characteristics include darker-coloured green leaves and a more compact growth habit (Kermani et al 2003;Liu et al 2007;Allario et al 2011).…”
mentioning
confidence: 99%